0203 Greater Change in Fecal Metabolome Associated with Lower Ability to Maintain Wakefulness During Sleep Restriction and Circadian Misalignment. (12th April 2019) - Sprecher, Kate E; Vargas, Fernando; Peña-Gonzaez, Antonio; Burke, Tina M; Depner, Christopher M; Dorrestein, Pieter C; Fleshner, Monika; Knight, Rob; Lowry, Christopher A; Turek, Fred W; Vitaterna, Martha H; Wright, Kenneth P
Abstract: Introduction: This study combined sleep restriction and circadian misalignment, and tested the association of fecal metabolome with the ability to maintain wakefulness and sleepiness/alertness. Methods: 15 healthy adults (5 female), mean (±SD) age 24.3 (±3.6), BMI 22.2 (±2.3) kg/m 2 completed an 18-day protocol twice, separated by 3 recovery days of unscheduled sleep at home. For each 18-day protocol, participants maintained habitual self-selected 8h sleep schedules for two weeks at home prior to completing a four-day laboratory visit with one sleep opportunity per day: 8h on night one, 3h on night two and 3h on mornings three and four. Sleepiness/alertness was tested every 3h during scheduled wakefulness. Ability to maintain wakefulness was tested with the Maintenance of Wakefulness Test (MWT). Self-reported sleepiness/alertness was tested with the Karolinska Sleepiness Scale (KSS) and a visual analog scale. Fecal samples were collected following the first and third sleep opportunities. Fecal metabolome was analyzed using ultra high-performance liquid chromatography coupled to a quadrupole-Orbitrap mass spectrometer. Fecal metabolome changes during sleep restriction and circadian misalignment were quantified by Canberra-Adkins distance. Association of within-subject fecal metabolome changes with sleepiness/alertness was tested with linear mixed effects models. Stability of individual differences in metabolome changes were quantified by intra-class correlation coefficient (ICC). Results: During combined sleep restriction and circadian misalignment, greater change in fecal metabolome was associated with significantly shorter MWT sleep onset latency (p=0.028, SE=4.94), and lower self-reported alertness (p=0.045, SE=15.51), but not with KSS. Fecal metabolome changes showed substantial trait-like stability (ICC 0.66). Conclusion: Greater within-subject change in the fecal metabolome was associated with lower ability to maintain wakefulness and alertness during sleep restriction and circadian misalignment. The gut microbiome may support the ability to maintain wakefulness during insufficient sleep and circadian misalignment, and could be a countermeasure target for safety-critical professions experiencing such conditions (e.g. military, health care). Support (If Any): Office of Naval Research MURI (N00014-15-1-2809); NIH/NCATS (UL1TR002535); CU Undergraduate Research Opportunities Grant. Contents are the authors' sole responsibility and do not necessarily represent official NIH views.